1985
DOI: 10.7164/antibiotics.38.9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic products of microorganisms. 228. New nikkomycins produced by mutants of Streptomyces tendae.

Abstract: Four new dipeptidyl nikkomycins of the Z-and the X-series with a variation in the amino acid moiety of the molecule were isolated from the mutant Streptomyces tendae 901/395 and characterized.Nikkomycins Kz and Kg contain 2-amino-4-hydroxy-4-(2-pyridyl)butyric acid, and nikkomycins Oz and Os 2-amino-4-hydroxy-4-(5-hydroxy-2-pyridyl)butyric acid. In contrast to nikkomycins Z and X, nikkomycins Kx, and 0x are quite stable at alkaline pH and exhibit a lower biological activity against various test organisms. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 6 publications
(1 reference statement)
0
17
0
Order By: Relevance
“…nikV insertion mutants were not able to form nikkomycins containing HPHT as the peptidyl moiety, but instead accumulated nikkomycins O z and O x , which contain a peptidyl moiety consisting of HPHT without the methyl group at carbon-3. These nikkomycins had previously been isolated from culture ®ltrates of the S. tendae mutant TuÈ 901/395 obtained after UV treatment (Bormann et al 1985). The phenotype of nikV mutants can be rationalized by assuming that a primary metabolite, presumably pyruvate, is used as an alternate substrate by NikB, yielding the peptidyl moiety of nikkomycins O x and O z .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nikV insertion mutants were not able to form nikkomycins containing HPHT as the peptidyl moiety, but instead accumulated nikkomycins O z and O x , which contain a peptidyl moiety consisting of HPHT without the methyl group at carbon-3. These nikkomycins had previously been isolated from culture ®ltrates of the S. tendae mutant TuÈ 901/395 obtained after UV treatment (Bormann et al 1985). The phenotype of nikV mutants can be rationalized by assuming that a primary metabolite, presumably pyruvate, is used as an alternate substrate by NikB, yielding the peptidyl moiety of nikkomycins O x and O z .…”
Section: Discussionmentioning
confidence: 99%
“…The strains were grown for 6 days in production medium. Peaks corresponding to nikkomycins C z , C x , O z , O x , Z, X, J, and I are indicated times and characteristic ultraviolet spectra, which were identical to those of reference substances (Bormann et al 1985). In addition to nikkomycins O z and O x (150 mg/l), nikV mutants accumulated the nucleoside moieties nikkomycins C z and C x (350 mg/l).…”
Section: Insertional Mutagenesismentioning
confidence: 93%
“…New nikkomycins have been found and isolated by using a photodiode array detector (Fiedler 1984) or mutation techniques (Delzer et al 1984;Bormann et al 1985). For many years it has been known that the strain Streptornyces tendae is able to produce juglomycins as well, Offprint requests to: D. Hege-Treskatis another group of antibiotics very different from nikkomycins (Langh~irig 1978;Werner 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the polyoxins, several derivatives with different amino acid or amino fatty acid compositions were prepared with the hope of improving uptake and biological activity (81,138,144,221,222). With the nikkomycins, the group led by H. Zahner used a different approach in that they first mutagenized the producing strain of Streptomyces tendae and then ran a directed fermentation providing pyrimidines, purines, imidazoles, or amino acids (24,25,66,67,69,101,114 Complicating the issue of differing susceptibilities is a recent report that suggests that, with S. cerevisiae, the gene products of CHSI and CHS2 show differential susceptibilities to the inhibitory effects of polyoxins and nikkomycins, with Chsl being more susceptible (34). As it has been confirmed that several different medically important fungi also have multiple forms of chitin synthetase (26), it is an obvious statement that a determination of the relative importance of each form to the growth of the cell must be made.…”
Section: Compounds Active Against Fungal Cell Walls Inhibitors Of Chimentioning
confidence: 99%